(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the legal foundations of parliamentary activity in the Republic of Uzbekistan within the context of ongoing constitutional reforms and the development of democratic governance. Particular attention is given to the principle of separation of powers, its theoretical underpinnings, and its practical implementation in the national system of state authority. The study analyzes the role of Parliament (Oliy Majlis) as a central institution in ensuring checks and balances among the branches of government. The article also explores the organizational and legal framework of the Parliament as defined in the updated Constitution of the Republic of Uzbekistan, highlighting recent changes aimed at strengthening parliamentary effectiveness and accountability. Special emphasis is placed on the core functions of Parliament, including its legislative role in law-making, its oversight (control) function over the executive branch, and its representative function in expressing the will and interests of the people.